Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10899-017-9726-y
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analytical Synthesis and Examination of Pathological and Problem Gambling Rates and Associated Moderators Among College Students, 1987–2016

Abstract: The problem of gambling addiction is especially noteworthy among college students, many of whom have the resources, proximity, free time, and desire to become involved in the myriad options of gambling now available. Although limited attention has been paid specifically to college student gambling in the body of literature, there have been three published meta-analyses estimating the prevalence of probable pathological gambling among college students. The research presented is the largest and most comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 81 publications
3
29
3
1
Order By: Relevance
“…Several recent systematic reviews and meta-analyses of the literature (mainly from highincome countries) have reported some key risks and correlates of problem gambling among young people, including being male, younger, psychological distress, substance use, child maltreatment, parental problem gambling (Dickson et al 2008;Dowling et al 2017;Griffiths and Parke 2010;Lane et al 2016;Nowak 2018;Shead et al 2011). Generally, even though gambling may provide some psychosocial benefits (Binde 2013), comparatively, problem gambling has been associated with various negative outcomes, including mental and physical health problems, relationship and family dysfunction, financial problems, employment difficulties, and legal issues (Blinn-Pike et al, 2010;Derevensky et al 2011;Derevensky and Gupta 2005a;Langhinrichsen-Rohling 2005;Shaffer and Hall 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent systematic reviews and meta-analyses of the literature (mainly from highincome countries) have reported some key risks and correlates of problem gambling among young people, including being male, younger, psychological distress, substance use, child maltreatment, parental problem gambling (Dickson et al 2008;Dowling et al 2017;Griffiths and Parke 2010;Lane et al 2016;Nowak 2018;Shead et al 2011). Generally, even though gambling may provide some psychosocial benefits (Binde 2013), comparatively, problem gambling has been associated with various negative outcomes, including mental and physical health problems, relationship and family dysfunction, financial problems, employment difficulties, and legal issues (Blinn-Pike et al, 2010;Derevensky et al 2011;Derevensky and Gupta 2005a;Langhinrichsen-Rohling 2005;Shaffer and Hall 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of the literature has reported that 7.89% of university students engage in pathological gambling, which is a significantly higher prevalence compared to both adolescents and adults (Blinn-Pike, Worthy, & Jonkman, 2007). A more recent meta-analysis conducted by Nowak (2018) showed that the high prevalence of probable pathological gambling and problem gambling among university students continues to be high (i.e., 6.13 and 10.23% respectively). Because GD is significantly, positively associated with various mental disorders, such as anxiety, depression, substance dependence, and Internet gaming disorder (IGD; Chen, Tong, Wu, Lau, & Zhang, 2018;Hartmann & Blaszczynski, 2018;Lorains, Cowlishaw, & Thomas, 2011;Scholes-Balog, Hemphill, Toumbourou, & Dowling, 2015), more attention should be paid to the psychological antecedents and consequences of gambling behaviors among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Gambling disorder (GD) is a significant public health problem affecting 0.4-1% of the US population, also being prevalent in many other countries. 1,2 Psychosocial impairment, financial and family problems, as well as elevated rates of suicide are common among individuals with GD. 3 GD can be conceptualized from a neurobiological perspective in terms of excessive drive from subcortical regions involved in reward processing coupled with diminished top-down control from prefrontal cortical regions.…”
Section: Introductionmentioning
confidence: 99%